P008: Evaluation of outcomes after implementation of a provincial prehospital bypass standard for trauma patients – an Eastern Ontario experience. (May 2019) - Austin, M.; Sinclair, J.; Leduc, S.; Duncan, S.; Rouleau, J.; Price, P.; Evans, C.; Vaillancourt, C.
Abstract : Introduction : Trauma and injury play a significant role in the population's burden of disease. Limited research exists evaluating the role of trauma bypass protocols. The objective of this study was to assess the impact and effectiveness of a newly introduced prehospital field trauma triage (FTT) standard, allowing paramedics to bypass a closer hospital and directly transport to a trauma centre (TC) provided transport times were within 30 minutes.Methods : We conducted a 12-month multi-centred health record review of paramedic call reports and emergency department health records following the implementation of the 4 step FTT standard (step 1: vital signs and level of consciousness, step 2: anatomical injury, step 3: mechanism and step 4: special considerations) in nine paramedic services across Eastern Ontario. We included adult trauma patients transported as an urgent transport to hospital, that met one of the 4 steps of the FTT standard and would allow for a bypass consideration. We developed and piloted a standardized data collection tool and obtained consensus on all data definitions. The primary outcome was the rate of appropriate triage to a TC, defined as any of the following: injury severity score ≥12, admitted to an intensive care unit, underwent non-orthopedic operation, or death. We report descriptive and univariate analysis where appropriate.Results : 570 adult patients were included with the following characteristics: mean age 48.8, male 68.9%, attended by Advanced Care Paramedic 71.8%, mechanisms of injury: MVC 20.2%, falls 29.6%, stab wounds 10.5%, median initial GCS 14, mean initial BP 132, prehospital fluid administered 26.8%, prehospital intubation 3.5%, transported to a TC 74.6%. Of those transported to a TC, 308 (72.5%) had bypassed a closer hospital prior to TC arrival. Of those that bypassed a closer hospital, 136 (44.2%) were determined to be "appropriate triage to TC". Bypassed patients more often met the step 1 or step 2 of the standard (186, 66.9%) compared to the step 3 or step 4 (122, 39.6%). An appropriate triage to TC occurred in 104 (55.9%) patients who had met step 1 or 2 and 32 (26.2%) patients meeting step 3 or 4 of the FTT standard.Conclusion : The FTT standard can identify patients who should be bypassed and transported to a TC. However, this is at a cost of potentially burdening the system with poor sensitivity. More work is needed to develop a FTT standard that will assist paramedics in appropriately identifying patients who require a trauma centre.